2000
DOI: 10.1039/a909714g
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of protein adducts of hexahydrophthalic anhydride and methylhexahydrophthalic anhydride in human plasma

Abstract: Hexahydrophthalic anhydride (HHPA) and methylhexahydrophthalic anhydride (MHHPA) are two highly allergenic compounds used in the chemical industry. A method was developed for quantification of protein adducts of HHPA and MHHPA in human plasma. The plasma was dialysed and the anhydrides were hydrolysed from the proteins at mild acidic conditions. The released hexahydrophthalic acid (HHP acid) and methylhexahydrophthalic acid (MHHP acid) were purified by reversed solid phase extraction followed by derivatisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…In fact, the obtained correlations were far better than any previously reported associations between exposure and adduct levels in general. In addition, as reported in an earlier study, we found high correlations between the TPPA levels and the adducts with merely the HSA in 10 workers with differing protein levels (22). Furthermore, in this study, we found a close correlation also between TPPA and the Hb adducts of HHPA.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In fact, the obtained correlations were far better than any previously reported associations between exposure and adduct levels in general. In addition, as reported in an earlier study, we found high correlations between the TPPA levels and the adducts with merely the HSA in 10 workers with differing protein levels (22). Furthermore, in this study, we found a close correlation also between TPPA and the Hb adducts of HHPA.…”
Section: Discussionsupporting
confidence: 76%
“…In this report we have used a recently developed method to quantify the levels of TPPA (22). This method is easy and convenient, and it dispenses with tedious, labor-intensive protein isolation steps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total plasma protein adducts of HHPA and MHHPA were quantified using a recently published gas chromatographic-mass spectrometric (GC-MS) method (9). Briefly, aliquots of plasma were dialyzed, and the adducted HHPA and MHHPA were hydrolyzed from the proteins to the corresponding acids.…”
Section: Exposure Assessmentsmentioning
confidence: 99%
“…However, despite the potential of protein adducts as biomarkers of exposure, development in the area has been remarkably slow, probably because of the rather laborious laboratory procedures coupled with the high costs of the equipment needed for analyzing the samples. Recently, we reported a convenient method for analyzing the total plasma protein adducts of HHPA and MHHPA (9) and showed that these adducts are excellent biomarkers of long-term exposure to the anhydrides (10).…”
mentioning
confidence: 99%